Income inequality and mass shootings in the United States - Roy Kwon; Joseph F. Cabrera (BMC, 2019)
Abstract Background Mass shootings are an increasingly common phenomenon in the United States. However, there is little research on whether the recent growth of income inequality is associated with this rise of mass shootings. We thus build on our prior research to explore the connection between income inequality and mass shootings across counties in the United States. Methods We assemble a panel dataset of 3144 counties during the years 1990 to 2015. Socioeconomic data are extracted from the U.S. Bureau of the Census. Mass shootings data are from three databases that compile its information from the Federal Bureau of Investigation and media sources, respectively. These data are analyzed using random effects negative binomial regressions, while controlling for seven additional predictors of crime. Results Counties experiencing a one standard deviation growth of income inequality witnessed 0.43 more mass shootings when using the definition of three or more victim injuries (incidence rate ratio [IRR] = 1.43; 95% confidence interval [CI] = 1.24, 1.66; P < .001) and 0.57 more mass shootings when using the designation of four or more victim deaths (IRR = 1.57; 95% CI = 1.26, 1.96; P < .001). Conclusions Counties with growing levels of income inequality are more likely to experience mass shootings. We assert that one possibility for this finding is that income inequality fosters an environment of anger and resentment that ultimately leads to violence.